Pediatric dumbbell-shaped orbital schwannoma with extension to the cranial cavity: A case report and literature review - Shao, Yongjia; Xi, Qian; Cheng, Ailan; Qian, Minghui; Chu, Shuguang (Frontiers in Neurology, 2023)
Orbital schwannomas in children are rare especially those with intracranial extension. Herein, our report refers to a 12-year-old boy who had a cranial-orbital mass with dumbbell-shaped appearance. The total neoplasm was successfully removed via a transcranial approach, and the result of pathological diagnosis was schwannoma. Neither radiotherapy nor chemotherapy was performed after surgery, and no evidence of recurrence was observed after three months. Our report suggests that orbital schwannomas should be differentiated from other types of orbital tumors with sufficient evidence, and complete surgical resection is still the first choice to heal this disease.